Imformation Technology Center Di Pekanbaru Dengan Pendekatan Arsitektur High Tech - Ary Surya Syahputera; Wahyu Hidayat; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Information Technology Center is a place which has function as a center for a place which including the technology for share information by using computer system which is usefull for human in the social condition, economy, and culture. Pekanbaru is a town which has high city activity in the area of commerce and service, so its need of information technology is high. Information Technology Center in Pekanbaru is a place which has been designed to accomodate the need in the area of information technology, therefore it use the theme Architecture High Tech. The concept which has been applied is the six characters of Architecture High Tech building, that is consisted of : (1) Inside out, the use of tranparent element; (2) Celebration of process, the exposed structure; (3) Transparent, layer, and movement; (4) Bright and flatten coloring; (5) A weight filigree of tensile member; (6) Optimistic confidence in a scientific cultura, that is the use of technology which is oriented to the future. By this design activity, it has been obtained the conclusion that in designing Information Technology Center, we need: (1) The clear division of the areas in the information technology, which later it will be the mass of the building; (2) The effective compilation of spaces; (3) The applying of architechture high tech which is started from the use of building material, structure, the expose of building technology system, the coloring which is based of function, and economical of energy technology.Key Words: Information Technology Center, High Tech Architecture.